2015
DOI: 10.1007/s00167-015-3667-8
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of two interscalene blocks and one cervical epidural block in arthroscopic rotator cuff repair

Abstract: Randomized controlled trials, Therapeutic study, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…To describe higher pain levels, the scales used 14 different anchors in total ( Figure 2 ) with “worst pain imaginable” [ 11 , 12 , 15 , 26 , 36 , 38 , 43 , 48 , 51 , 54 ] being the preferred anchor. The second most frequent anchor was “worst pain” [ 10 , 28 , 33 , 34 ] and then successively “most severe pain imaginable” [ 19 , 20 , 37 ], “severe pain” [ 18 , 32 , 46 ], and “worst possible pain” [ 29 , 41 , 47 ]. Twelve studies did not report the used anchors [ 13 , 16 , 17 , 27 , 31 , 35 , 40 , 49 , 50 , 55 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To describe higher pain levels, the scales used 14 different anchors in total ( Figure 2 ) with “worst pain imaginable” [ 11 , 12 , 15 , 26 , 36 , 38 , 43 , 48 , 51 , 54 ] being the preferred anchor. The second most frequent anchor was “worst pain” [ 10 , 28 , 33 , 34 ] and then successively “most severe pain imaginable” [ 19 , 20 , 37 ], “severe pain” [ 18 , 32 , 46 ], and “worst possible pain” [ 29 , 41 , 47 ]. Twelve studies did not report the used anchors [ 13 , 16 , 17 , 27 , 31 , 35 , 40 , 49 , 50 , 55 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pain ratings were specified to be at rest or during activity in 11 studies [ 10 , 13 , 16 , 23 , 26 28 , 32 , 44 , 55 , 58 ], of which 3 studies [ 10 , 16 , 26 ] specified pain to be exclusively measured at rest. Eight out of the 11 studies described pain during activity and the definitions were: movement during cough and mobilization [ 27 ], motion attempts [ 28 ], shoulder movements [ 58 ] during activities such as dressing or during transfer from lying to sitting [ 23 ], passive motion [ 55 ], during overhead activities and sleep [ 44 ]; two studies did not specify the activity [ 13 , 32 ]. The remaining 36 studies did not specify whether pain was measured during activity or at rest.…”
Section: Resultsmentioning
confidence: 99%
“…ANB has also been adopted for shoulder pain control and is mainly used in combination with SSNB [2,11,13,22]. There are a couple of studies which compare a regional block with epidural or spinal block [8,9]. One study reported that ultrasound-guided continuous ISB using 0.2 % ropivacaine may provide superior post-operative analgesia compared to ultrasound-guided continuous ISB using 0.75 % ropivacaine or fluoroscopy-guided targeted continuous cervical epidural block in arthroscopic cuff repair [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it allows one to reduce the dose of LA [1], shortens the time of the onset of RA [2], minimises the rate of failed blocks [3] and the occurrence of brachial plexopathy [4], as well as the frequency of other unwelcome adverse events, such as intravascular injections of cardio-or neurotoxic LA [5], and diaphragm paralysis [6,7] with respiratory disorder [8]. In the end, IPBP produces appropriate analgesia for the postoperative period compared with general anaesthesia, which improves patients' satisfaction [9,10].…”
mentioning
confidence: 99%